The Effectiveness of the Instrumental Enrichment Strategy in the Mental Mathematics for the Fifth primary Grade Female pupils - Salih Abdullah, Mudrika; Jabbar Abdullh, Noor (Opción, 2019)
The current study aimed at knowing the effectiveness of the Instrumental Enrichment Strategy in the Mathematics Mental for the Fifth primary Grade Female pupils. The sample of the study consisted of (57) female students from the fifth-grade primary school, the sample of the study was randomly divided into two groups, one of which was the experimental group consisted of (29) pu- pils and another was control group consisted of (28) pupils. The experimental design with the partial control was used for two equivalent groups with a post- test. A test of mental mathematics was adopted, consisting of (30) paragraphs of a multiple-choice type with four alternatives, divided into three compo- nents (Mental Computation, Rough Estimation, Mathematical intuition). The reliability of the tool and the Psychometric properties were verified, and the stability was calculated using Kuder-Richardson 20 (K-R20), equation. The results were processed using the t-test for two independent samples and the Mac Gujian Effectiveness Equation was also used. The results showed there is statistically significant difference at the level of significance (0.05) between the mean of two groups (experimental and control) in the mental mathematics test.